Solution of Modern Thermo Physical Problems of Applied External and Internal Aerodynamics with Dark Matter-Energy Simulation: Scientific Explanation - Mikhail Ja. Ivanov (New Approaches in Engineering Research Vol. 11, 2021)
The work is dedicated to new, experimentally verified thermophysical problems of high temperature applied exterior and internal aerodynamics, which is characterised first and foremost by intense interaction of gaseous media and heat radiation. The first section of the research delves into the fundamental problems of constructing high-temperature air breathing engines, namely origin of so-called "unexpected" heat generated during the working process. The report’s next sections look at the physical, chemical, and plasma characteristics of reentry space blunt bodies and meteors’ aerodynamics, with a focus on the influence of thermal radiation. Our solutions are based on the well-known Dark Matter-Energy model. We give unique experimental evidence for registering Dark Matter pressure under Earth settings.